Women's Health and Modern Gynecology (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Nongenetic environmental factors contribute to maternal morbidity and mortality from chemical exposures through air, water, soil, food, and consumer products. Pregnancy is a particularly sensitive period of susceptibility during which physiological changes in every major organ system increase sensitivity to chemicals that may affect a woman’s long-term health. Nonchemical stressors, such as low socioeconomic status, may exacerbate the effects of chemicals on maternal health. Racial/ethnic minorities are disproportionately exposed to both chemical and nonchemical stressors, which likely contribute to observed disparities in maternal morbidity and mortality. Epidemiologic studies linking exposures to adverse maternal health outcomes highlight the importance of environmental exposures on health, and mechanistic studies in model systems reveal how chemicals disrupt biological pathways and processes. Environmental stressors have been linked to a range of immediate maternal health effects, including hypertension disorders during pregnancy, fibroids, and infertility, as well as long-term maternal health effects, such as increased risk of breast cancer and metabolic disorders. Identifying and reducing a pregnant woman’s environmental exposure is not only beneficial for her offspring, but is also important for her short- and long-term health.